From Tradition to Modernity: Transformation of The Practice of Marriage Agreement in Indonesia - Afiq Budiawan; Yahanan Yahanan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
This study aims to analyze the practice of marriage agreements in Indonesia in the perspective of Islamic law and positive law, as well as identify the factors that influence it. The research method used is qualitative with the approach Empirical law, involving interviews with notaries, ministries of the Ministry of Religion, and couples who made a marriage agreement in DKI Jakarta, East Java, Riau, and the Regency/City of Malang. The results showed that marriage agreements in Indonesia are still limited to the separation of assets and are widely carried out by couples with high legal awareness. Factors that influence this practice include economy, education, culture, and modernization. The main recommendation of this research is the need for regulatory renewal in the Marriage and KHI Law so that the marriage agreement can include aspects of the protection of the rights of couples more broadly, as well as further socialization by the Ministry of Religion to change the perception of the community regarding the marriage agreement